Growth performance of maize (Zea Mays) in the initial stage under shallow water conditions to determine the best planting season in lowland area - D, Ramawulan; Momon manudin, Sodik; Bakri, Bakri (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Maize crop is one of the agricultural commodity crops that have an important role in the agricultural sector because corn plants are needed in the supply of food, feed, livestock and other industrial needs. The condition of corn plants with high rainfall can result in the risk of flooding of corn plants, if the corn plants are always flooded continuously it will result in a decrease in corn production. Stagnant water is an abiotic stress that must be considered because it can result in an increase in H2O and a decrease in O2 in stagnant plants. Stagnant water or excessive water stress can result in decreased plant development and decreased production. The aim of the research was to look at the growth conditions of maize plants at various high groundwater levels. The best expansion was achieved in treatment P5 (groundwater table 30 cm from the soil surface) that is 212.67 cm and the lowest results were in treatment P2 (groundwater table 5 cm from the soil surface) with a plant height of 61.50 cm